Deficiencia de Boro en Plantaciones de Pinus radiata D. Don en Chile I. Distribución y Origen - Schlatter, J. E.; Gerding S., Victor (Bosque (Valdivia), 1985)
Boron deficiency makes one of the most important and widely distributed nutritional in Pinus radiata D. Don plantation s within Central Chile. It is usually present in soils derived from granitic rocks and volcanic materials. The problem becomes worser when soils have lost much of its organic matter reserve, mainly be erosion, what means a lower water retention capacity and a lower boron availability. It is more serious if the plantation is located in districts with low annual rainfall and/or a long dry season.